A systematic review on the off-label use of montelukast in atopic dermatitis treatment - Chin, Weng Khong; Lee, Shaun Wen Huey (International journal of clinical pharmacy, 2018)
Background Atopic dermatitis (AD) is the most common form of eczema. As leukotriene mediators are involved in the inflammatory phase of atopic dermatitis, montelukast has been suggested as a possible therapy. Aim of the review To evaluate the safety and efficacy of montelukast off-label use for the treatment atopic dermatitis. Method A search was performed from database inception until March 2018 in six electronic databases for randomized-controlled-trials examining the use of montelukast for AD. Results Among 301 articles screened, 11 studies met the inclusion criteria and were included in the review. The study populations consist of paediatric and adult subjects with moderate-to-severe AD. Montelukast use was shown to improve symptoms such as pruritus in four studies. Another 2 studies reported that montelukast could improve symptoms similar to the standard regimen of topical steroid and oral antihistamine. However, five studies reported that montelukast had no effects in symptoms alleviation. The use of montelukast was associated with a similar safety profile to placebo and well-tolerated with minimal adverse effects. Conclusion There is limited evidence to suggest that the off-label use of montelukast is effective in treating moderate-to-severe AD. Further research with larger study populations employing standardized endpoint measuring instrument is warranted to further investigate the off-label use of montelukast in AD treatment. Until then, the use of conventional treatments including optimal daily skin hydration should remain the mainstay in the management of atopic dermatitis. In fact, for moderate-to-severe condition, steroid sparing immune-suppressants should still be used clinically until more effective and safer alternative is discovered.